2019
DOI: 10.1002/jcla.22856
|View full text |Cite
|
Sign up to set email alerts
|

Determination of hemolysis index thresholds for biochemical tests on Siemens Advia 2400 chemistry analyzer

Abstract: BackgroundIn vitro hemolysis is still the most common source of pre‐analytical nonconformities. This study aimed to investigate the hemolytic effects on commonly used biochemical tests as well as to determine the hemolysis index (HI) thresholds on Siemens Advia 2400 chemistry analyzer.MethodsPeripheral blood samples were collected from forty healthy volunteers. Hemolysis was achieved using syringes. Five hemolysis levels were produced including the no hemolysis group, slight hemolysis group, mild hemolysis gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 21 publications
0
13
2
Order By: Relevance
“…It is well known that the hemolysis index is an extremely useful indicator that quantitatively evaluates the hemolysis of blood cells 16‐18 . The hemolytic interference revealed markedly significant regression and very high correlation coefficients with the measured hemolysis indices.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…It is well known that the hemolysis index is an extremely useful indicator that quantitatively evaluates the hemolysis of blood cells 16‐18 . The hemolytic interference revealed markedly significant regression and very high correlation coefficients with the measured hemolysis indices.…”
Section: Resultsmentioning
confidence: 94%
“…For hemolysis interference, the results of quantitative analysis are largely consistent with previous reports, including changes in LDH, potassium, CK, CK-MB, and some other analytes. 12,18,19 However, several previous studies used freeze-and-thaw or mechanical trauma without assessing the achievement of cell lysis. 12,16,20,21 In these studies, the extent of hemolysis was solely determined from the hemolytic index measured by the machine.…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings were incompatible with this information. In other studies, it has been reported that the values given by the manufacturer are not compatible with their results (27,28). On the other hand, interferograms are recommended in clinical chemistry tests for managing haemolysed specimens (11,21).…”
Section: Discussionmentioning
confidence: 96%
“…It was observed that the findings within the reference range obtained in this study were consistent with our findings, and in the same study, it was stated that the manufacturer's statements were insufficient for ALT tests, among the tests evaluated. Studies on other devices and reagents have also obtained results that do not comply with the manufacturer's declarations (21)(22)(23)(24). On the other hand, the general approach assumes the significant change affecting the result as ± 10% and presents the cut-off values accordingly.…”
Section: Discussionmentioning
confidence: 99%